Design and fabrication of MS88 fiberglass helmet - Mohd Nazmi, Mohd Nordin (2007)
The fabrication of MS88 fibre glass helmet project was focused in design and fabricates the fibreglass helmet. The design of mould based on MS88 design helmet. The mould use polystyrene material coated by aluminium foil. Using the fibreglass as a main material for fabrication, it can reduce the mass of the helmet and increase the conformability to wear. The process to fabricate the fibreglass helmet is called "lay up" process where the fibreglass mat is applied on the mould layer by layer with the mixture of 99% of polyester resin and 1 % of hardener. However the surface of fibre glass helmet is not smooth enough because of the sphere shape of mold make it hard to apply the fibreglass mat. After the helmet was fabricated, the samples of fibreglass are tested using Compression Testing machine to measure the mechanical properties of fibreglass reinforce plastic(FRP). The overall project can be described as successfully project because the MS88 fibreglass helmet manages to fabricate in the time given.